Influence of pulp-preconditioning and fermentation on fermentative quality and appearance of ghanaian cocoa (theobroma cacao) beans - Afoakwa, E.O.; Jennifer, Q.; Agnes, S.B.; Jemmy, S.T.; Firibu, K.S. (International Food Research Journal, 2012)
Studies were conducted to evaluate effects of pod storage (as a means of pulp pre-conditioning) and fermentation time on the fermentative quality and appearance of Ghanaian cocoa beans. The fermentative quality (cut test and fermentation index [FI]) and colour (L, a, b) of the cocoa beans were studied using standard methods. Increasing pod storage and fermentation time significantly (P<0.05) influenced the fermentative quality and appearance of the beans. Fermentation caused significant increases in FI at all periods of pod storage whilst increasing pod storage resulted in darker, yellower and less red beans. Cut test scores revealed that storage of pods for 7 and 14 days increased the percentage of brown beans by 15 and 38% respectively by the sixth day of fermentation. Thus, Ghanaian cocoa pods could be stored for up to 14 days prior to fermentation with optimum fermentative quality and desired colour attained after 4 days of fermentation. © 2008 IFRJ, Faculty of Food Science & Technology, UPM.
Keywords: Bean colour; Cut test; Fermentation index; Forastero; Pod storage; Theobroma cacao